Aberration compensation and resolution improvement of focus modulation microscopy. (19th December 2016) - Zheng, Juanjuan; Gao, Peng; Shao, Xiaopeng
Abstract: Confocal laser scanning microscopy (CLSM) has wide applications in biological research and medical diagnosis. However, the spatial resolution and signal to noise ratio (SNR) of CLSM is reduced in the presence of an aberration. Here we improve the pupil-segmentation method to measure and compensate for aberrations in focus modulation CLSM (FM-CLSM), which uses Gaussian-type and doughnut-like foci to scan a sample in sequence. As a result, FM-CLSM can provide images with a high resolution and a high SNR for biomedical or industrial applications.